GAMBARAN KEPUASAN PASIEN TERHADAP PELAYANAN KESEHATAN GIGI DAN MULUT DI PRAKTEK DOKTER GIGI BERSAMA X KOTA BANDUNG (Politeknik Kesehatan Kemenkes Bandung, 2020)
Joint Dental Clinic X in Bandung as a dental health service facility that being a benchmark of the success of health development should be able to provide good quality services so that it can provide satisfaction to patients. Patient satisfaction is obtained if the services provided meet the expectation. This study aims to determine the level of patient satisfaction with dental and oral health services at the Joint Dental Clinic X in Bandung. This study is a descriptive study to see the patient’s satisfactions of dental and oral health care. The study was conducted in March 2020. Research using primary data obtained directly from the source of information with questionnaire list and interviews. Sampling techniques were carried out using a total sampling technique with a sample of 23 respondents. Data processing is performed quantitatively with value weighted criteria using Likert scale and data analysis using percentage analysis of all answers filled in by respondents. The results of study on patient satisfaction with dental and oral health services at the Joint Dental Clinic X City in Bandung described that patient satisfaction with the satisfaction of health personnel competence in providing services with a percentage score of 91,09%, clarity of action/treatment with a percentage number of score 93,04%, towards the empathy attitude of health workers with a percentage of 91,23% which according to the Likert scale criteria was included in the criteria of being very satisfied. Keywords: Level of Satisfaction, Health Services